2016
DOI: 10.1073/pnas.1611995113
|View full text |Cite
|
Sign up to set email alerts
|

MRG15 is required for pre-mRNA splicing and spermatogenesis

Abstract: Splicing can be epigenetically regulated and involved in cellular differentiation in somatic cells, but the interplay of epigenetic factors and the splicing machinery during spermatogenesis remains unclear. To study these interactions in vivo, we generated a germline deletion of MORF-related gene on chromosome 15 (MRG15), a multifunctional chromatin organizer that binds to methylated histone H3 lysine 36 (H3K36) in introns of transcriptionally active genes and has been implicated in regulation of histone acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 56 publications
4
45
2
Order By: Relevance
“…C. elegans HDA-1 is one of three class I histone deacetylases (HDACs) in C. elegans and a component of several other chromatin complexes, as in other species (Kelly and Cowley, 2013;Passannante et al, 2010). MRG-1, the C. elegans counterpart of the chromo-domain (CD) protein Eaf3/MRG15, is also found in additional chromatin complexes (Bleuyard et al, 2017;Chen et al, 2010;Huang et al, 2017;Iwamori et al, 2016;Smith et al, 2013), and ATHP-1 (AT Hook plus PHD finger transcription factor), a counterpart of Rco1/Pf1, contains an AT Hook domain that is not found in either Rco1 or Pf1 ( Figure S2D).…”
Section: Elegans Homologs Of the Sin3s Complex Copurify With Cfp-1mentioning
confidence: 99%
“…C. elegans HDA-1 is one of three class I histone deacetylases (HDACs) in C. elegans and a component of several other chromatin complexes, as in other species (Kelly and Cowley, 2013;Passannante et al, 2010). MRG-1, the C. elegans counterpart of the chromo-domain (CD) protein Eaf3/MRG15, is also found in additional chromatin complexes (Bleuyard et al, 2017;Chen et al, 2010;Huang et al, 2017;Iwamori et al, 2016;Smith et al, 2013), and ATHP-1 (AT Hook plus PHD finger transcription factor), a counterpart of Rco1/Pf1, contains an AT Hook domain that is not found in either Rco1 or Pf1 ( Figure S2D).…”
Section: Elegans Homologs Of the Sin3s Complex Copurify With Cfp-1mentioning
confidence: 99%
“…Strikingly, two spermatogenic cell types (spermatocytes and spermatids) are responsible for most of the AS isoform complexity found in the testis (Soumillon et al, 2013). The functions and regulation of AS in these and other spermatogenic cells is just beginning to be understood (O'Bryan et al, 2013;Schmid et al, 2013;Iwamori et al, 2016;Hannigan et al, 2017). Using available RNA-sequencing (RNA-seq) data from spermatogonia, spermatocytes, round spermatids, and spermatozoa (Soumillon et al, 2013), we previously identified 1030 stagespecific changes in AS mRNA isoforms as germ cells move through the spermatogenic pathway (affecting expression of 912 genes) (Hannigan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Histone H3K36 methylation regulates pre-mRNA splicing in S. cerevisiae (Sorenson et al, 2016), and MRG15, which forms a complex with ASH1L (Lee et al, 2019), also regulates pre-mRNA splicing (Iwamori et al, 2016). Since ASH1L dimethylates H3K36 (Miyazaki et al, 2013;Zhu et al, 2016a) and forms a complex with MRG15, we asked if ASH1L could regulate the alternative splicing of NTRK2 (TrkB) mRNA, which has seven distinct splicing isoforms.…”
Section: Ash1l Specifically Regulates the Expression Of The Neurotropmentioning
confidence: 99%